Green mars - Robinson, Kim Stanley (Robinson, Kim Stanley. Mars trilogy, 2021)
"In the Nebula Award winning Red Mars, Kim Stanley Robinson began his critically acclaimed epic saga of the colonization of Mars, Now the Hugo Award winning Green Mars continues the thrilling and timeless tale of humanity's struggle to survive at its farthest frontier.